Recognition of Melanocytes in Immuno-Neuroendocrinology and Circadian Rhythms: Beyond the Conventional Melanin Synthesis - Yan-Yan Chen; Li-Ping Liu; Hang Zhou; Yun-Wen Zheng; Yu-Mei Li (Cells, 2022)
Melanocytes produce melanin to protect the skin from UV-B radiation. Notwithstanding, the spectrum of their functions extends far beyond their well-known role as melanin production factories. Melanocytes have been considered as sensory and computational cells. The neurotransmitters, neuropeptides, and other hormones produced by melanocytes make them part of the skin’s well-orchestrated and complex neuroendocrine network, counteracting environmental stressors. Melanocytes can also actively mediate the epidermal immune response. Melanocytes are equipped with ectopic sensory systems similar to the eye and nose and can sense light and odor. The ubiquitous inner circadian rhythm controls the body’s basic physiological processes. Light not only affects skin photoaging, but also regulates inner circadian rhythms and communicates with the local neuroendocrine system. Do melanocytes “see” light and play a unique role in photoentrainment of the local circadian clock system? Why, then, are melanocytes responsible for so many mysterious functions? Do these complex functional devices work to maintain homeostasis locally and throughout the body? In addition, melanocytes have also been shown to be localized in internal sites such as the inner ear, brain, and heart, locations not stimulated by sunlight. Thus, what can the observation of extracutaneous melanocytes tell us about the “secret identity” of melanocytes? While the answers to some of these intriguing questions remain to be discovered, here we summarize and weave a thread around available data to explore the established and potential roles of melanocytes in the biological communication of skin and systemic homeostasis, and elaborate on important open issues and propose ways forward.